Performance Analysis of a Multi Seed Smart Dryer Machine for Drying Peanuts (Arachis hypogaea L.) - Soekarno, Siswoyo; Firdiyanti, Fina; Harsono, Soni Sisbudi; Marhaenanto, Bambang (The University of Lampung, 2024)
Peanuts are the second largest legume crop in Indonesia, both cultivated on farms and wild. In 2019-2023, Indonesia experienced a decline in peanut production due to the declining in harvesting area. In addition, this is also due to the poor quality of seeds in the cultivation process. This study aims to observe the performance of the Multi Seed Smart Dryer (MSSD) machine for peanut seeding. This research was conducted by observing changes in moisture content, drying rate, drying temperature, and peanut germination test results using the Multi Seed Smart Dryer machine. The results showed that the left side of all shelves experienced an increase in temperature because it was close to the heat source and the level of temperature uniformity was still said to be uniform because it did not exceed the uniformity limit. The peak drying rate occurred at the 12th hour and decreased further. Based on the results of the germination test, the dried beans have a germination rate of 83%. This is in accordance with the passing standard of seed quality according to the Ministry of Agriculture of the Republic of Indonesia and International Seed Testing Association. Keywords: Drying, Multi Seed Smart Dryer, Peanut, Temperature.